2021
DOI: 10.3389/fonc.2020.590356
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Options of First-Line Tyrosine Kinase Inhibitors and Subsequent Systemic Chemotherapy Agents for Advanced EGFR Mutant Lung Adenocarcinoma Patients: Implications From Taiwan Cancer Registry Cohort

Abstract: ObjectivesLarge-scale, population-based real-world studies on the treatment outcomes of first-line tyrosine kinase inhibitors (TKIs) and subsequent systemic chemotherapy agents for lung adenocarcinoma (with activating epidermal growth factor receptor [EGFR] mutations) remain limited.Materials and MethodsFrom March 2014 to December 2016, patients with advanced lung adenocarcinoma, identified from the Taiwan Cancer Registry were included in this study if they received any of the three TKIs as first-line treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 50 publications
(75 reference statements)
0
10
0
Order By: Relevance
“…The enrolled population was identified, and their basic profile, underlying diseases, and use of chemotherapy or oral UFT were determined from the National Health Insurance Research Database (NHIRD) in Taiwan 25,26,28,29 . Meanwhile, the information of mortality was obtained from the Department of Statistics, Taiwan.…”
Section: Methodsmentioning
confidence: 99%
“…The enrolled population was identified, and their basic profile, underlying diseases, and use of chemotherapy or oral UFT were determined from the National Health Insurance Research Database (NHIRD) in Taiwan 25,26,28,29 . Meanwhile, the information of mortality was obtained from the Department of Statistics, Taiwan.…”
Section: Methodsmentioning
confidence: 99%
“…Pemetrexed is an anti-folic acid drug that can interfere with folic acid metabolism, resulting in aberrant DNA synthesis in tumor cells ( 144 ). A cancer registration cohort analysis from Taiwan showed that pemetrexed may be suitable as a first choice for chemotherapy in patients undergoing chemotherapy after progression with EGFR-TKI treatment ( 145 ). A 2018 meta-analysis showed that second-line drugs combined pemetrexed chemotherapy resulted in a longer PFS and OS duration than therapy with pemetrexed ( 146 ).…”
Section: Treatment Of T790m-negative Tumors After the Development Of ...mentioning
confidence: 99%
“…The dataset we used is a population-based registry system, Taiwan Cancer Registry (TCR), which includes over 90% of all cancer patients in Taiwan [23][24][25]. We retrieved patients with early-stage NSCLC identi ed by pathological con rmation, including those in stages IB and IIA (without any lymph node involvement) from the TCR during January 2011 and December 2017.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…The enrolled population was identi ed, and their basic pro le, underlying diseases, and use of chemotherapy or oral UFT were ascertained from the Taiwan NHI database [24,25,27,28]. Meanwhile, the information of mortality was obtained from the Department of Statistics, Taiwan.…”
Section: Study Design and Patientsmentioning
confidence: 99%
See 1 more Smart Citation